Grace's guide : the art of pretending to be a grown-up - Helbig, Grace (Simon & Schuster, 2014)
"A tongue-in-cheek handbook for millennials, encompassing everything a young or new (or regular or old) adult needs to know, from surviving a breakup to recovering from a hangover, ... [featuring] interactive elements and exclusive stories from Grace's own misadventures--like losing her virginity solely because her date took her to a Macaroni Grill--and many other hilarious lessons she learned the hard way"--